Bounds for solutions of nonlinear singular interface problems on time scales using a monotone iterative method - D. K. K. Vamsi; Pallav Kumar Baruah (Electronic Journal of Differential Equations, 2010)
In this article, we give bounds for solutions to initial-value problems associated with nonlinear singular interface problems. The singular interface problem is described using a pair of dynamic equations on a time scale. The method of upper and lower solutions intertwined with monotone iterative technique is used.